ISLAM DAN PERUBAHAN POLITIK - Jamal Ghofir (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2017)
When the internal Muslims have not been thorough in doing the equation of perception in the interpretation of Islamic political concepts. Already faced with foreign interests and interference in the agitation and propaganda of political concepts that refer to the Western political system. It is also a very difficult challenge for Muslims to implement and apply Islamic political concepts, even within the predominantly Muslim country.